2002
DOI: 10.1002/chir.10092
|View full text |Cite
|
Sign up to set email alerts
|

Survey of factors determining the circularly polarised luminescence of macrocyclic lanthanide complexes in solution

Abstract: The development of emissive lanthanide complexes as structural or reactive probes to signal changes in their local chiral or ionic environment has been inhibited by the lack of understanding of correlating structural and electronic spectral information. The definition of relatively rigid enantiopure macrocyclic lanthanide complexes, whose inter- and intramolecular exchange dynamics have been defined, offers scope for remedying this situation. Chiral axially symmetric lanthanide complexes in solution give rise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 14 publications
4
57
1
Order By: Relevance
“…This is in agreement with established theory on the topic of lanthanidebased CPL phenomena, which allows the emission dissymmetry factor to be related to size and relative orientations of the electric and magnetic dipole transition moments, µ and m, associated with a given transition (see Section 1.2.2). 92 This relationship is expressed in equation 8, where τ is the angle between the magnetic and electric transition dipole moments.…”
Section: Studies Using Circular Dichroismmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in agreement with established theory on the topic of lanthanidebased CPL phenomena, which allows the emission dissymmetry factor to be related to size and relative orientations of the electric and magnetic dipole transition moments, µ and m, associated with a given transition (see Section 1.2.2). 92 This relationship is expressed in equation 8, where τ is the angle between the magnetic and electric transition dipole moments.…”
Section: Studies Using Circular Dichroismmentioning
confidence: 99%
“…It has been suggested that for such complexes changes in the angle of twist about the principal axis and variations in the local ligand field (particularly the polarizability of any axial donor) will both lead to modulation of the total emission and/or CPL output and therefore changes in observed g em values. 92 In particular, the CPL is predicted to follow a sin4θ dependence for such complexes, where θ is the angle of twist about the principal axis. Hence, a twist angle of 0 o or 45 o will result in no CPL, whilst CPL will be at its highest when θ = ± …”
mentioning
confidence: 99%
“…Lanthanide complexes often show isostructurality along the series; this means that the geometry of the system may show no significant dependence on the lanthanide ion. 64 A nonchirooptical method to asses isostructurality is through analysis of the NMR data; in fact, paramagnetic shifts and relaxation rates of paramagnetic Ln 3+ compounds contain geometric information.…”
Section: Static Couplingmentioning
confidence: 99%
“…The PERSEUS output pointed out that the structure is a twisted square antiprism (TSA) with a twist angle of 22.9° meaning that the coordination polyhedron itself is chiral and it may account for the high luminescence dissymmetry factor that we observed. 33 3 with respect to axial coordination was further investigated by testing them with DMSO which has a strong affinity for Ln 3+ . Indeed, upon adding increasing quantities of DMSO to the mixture of tris/tetrakis Pr compounds, the water resonance recovered its standard shift at 2.13 ppm, DMSO resonance resulted shifted upfield, in accordance with axial coordination to Pr.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%